Analysis of Masterplan in Medan City Determining the Strategic Area (KSK) Social Culture Fields in Medan - Jehan Ridho Izharsyah; Faizal Hamzah Lubis (Budapest International Research and Critics University, 2020)
The City Strategic Area (KSK) is a strategic area compiled by the City in developing the area as seen from aspects of the Economy, Social Culture, the environment and others. Medan City Government through the Regional Planning and Development Agency of Medan City Establishes several Strategic Areas in Medan City through the 2016-2021 Regional Spatial Plan (RTRW) of Medan City including the Social and Cultural Strategic Area (KSK). This study uses a research method with a qualitative descriptive approach.Among them are Identification of Potential and Problems, Program Identification and using P3 (Arrangement, Supervision and Coaching). The research results show that the Medan City Government has implemented P3 through the elaboration of the RTRW trip that has been running for 4 years. However, it is still constrained by the process of guidance and supervision. Because some of these regional assets are not fully owned by the City Government but are owned by tribes and companies. Based on SWOT analysis Strength 1.26 while weakness factor 1.23 and Opportunity with a total score of 1.84 while Challenge 1.85, then the placement of cartesius diagrams of several Strategic Cities that are the locations of research are in Diversification Strategy which means the City Strategic Area Supervision (SCC) has the potential to be developed but still some need to be prepared strategically and improve management by the Medan City Government.